Decreased levels of active uPA and KLK8 assessed by [111In]MICA‐401 binding correlate with the seizure burden in an animal model of temporal lobe epilepsy. (19th July 2017) - Missault, Stephan; Peeters, Lore; Amhaoul, Halima; Thomae, David; Van Eetveldt, Annemie; Favier, Barbara; Thakur, Anagha; Van Soom, Jeroen; Pitkänen, Asla; Augustyns, Koen; Joossens, Jurgen; Staelens, Steven; et al.
Summary: Objective: Urokinase‐type plasminogen activator (uPA) and kallikrein‐related peptidase 8 (KLK8) are serine proteases that contribute to extracellular matrix (ECM) remodeling after brain injury. They can be labelled with the novel radiotracer [ 111 In]MICA‐401. As the first step in exploring the applicability of [ 111 In]MICA‐401 in tracing the mechanisms of postinjury ECM reorganization in vivo, we performed in vitro and ex vivo studies, assessing [ 111 In]MICA‐401 distribution in the brain in two animal models: kainic acid–induced status epilepticus (KASE) and controlled cortical impact (CCI)–induced traumatic brain injury (TBI). Methods: In the KASE model, in vitro autoradiography with [ 111 In]MICA‐401 was performed at 7 days and 12 weeks post‐SE. To assess seizure burden, rats were monitored using video‐electroencephalography (EEG) for 1 month before the 12‐week time point. In the CCI model, in vitro autoradiography was performed at 4 days and ex vivo autoradiography at 7 days post‐TBI. Results: At 7 days post‐SE, in vitro autoradiography revealed significantly decreased [ 111 In]MICA‐401 binding in hippocampal CA3 subfield and extrahippocampal temporal lobe (ETL). In the chronic phase, when animals had developed spontaneous seizures, specific binding was decreased in CA3 and CA1/CA2 subfields of hippocampus, dentate gyrus, ETL, and parietal cortex. Of interest, KASE rats with the highest frequency of seizures had the lowest hippocampal [ 111 In]MICA‐401 binding ( r = −0.76, p ≤ 0.05). Similarly, at 4 days post‐TBI, in vitro [ 111 In]MICA‐401 binding was significantly decreased in medial and lateral perilesional cortex and ipsilateral dentate gyrus. Ex vivo autoradiography at 7 days post‐TBI, however, revealed increased tracer uptake in perilesional cortex and hippocampus, which was likely related to tracer leakage due to blood–brain barrier (BBB) disruption. Significance: Strong association of reduced [ 111 In]MICA‐401 binding with seizure burden in the KASE model suggests that analysis of reduced levels of active uPA/KLK8 represents a novel biomarker candidate to be explored as a biomarker for epilepsy severity. However, limited BBB permeability of [ 111 In]MICA‐401 currently limits its application in vivo.